Strokes in Patients With Injection Drug Use and Tricuspid Valve Endocarditis – A Case Series. (July 2023) - Hingorani, Karan S.; Barnes, Erin; Carneiro, Thiago; Sader, Elie; Anand, Pria; Ong, Charlene J.; Chung, David; Daneshmand, Ali; Suchdev, Kushak; Takahashi, Courtney; Greer, David; Shulman, Julie G.; et al.
Research Design: In this study, we describe patients from a tertiary care safety-net hospital endocarditis registry with tricuspid valve infective endocarditis (TVIE), and concomitant acute or subacute ischemic stroke predominantly associated with injection drug use (IDU). We retrospectively obtained data pertinent to neurologic examinations, history of injection drug use (IDU), blood cultures, transthoracic/transesophageal echocardiography (TTE/TEE), neuroimaging, and Modified Rankin Scale (mRS) scores at discharge. Only those patients with bacteremia, tricuspid valve vegetations, and neuroimaging consistent with acute to subacute ischemic infarction and microhemorrhages in two cases were included in this series.Results: Of 188 patients in the registry, 66 patients had TVIE and 10 of these were complicated by ischemic stroke. Neurologic symptoms were largely non-specific, eight patients had altered mental status and only 3 had focal deficits. Nine cases were associated with IDU. Two patients had evidence of a patent foramen ovale on echocardiography. Blood cultures grew S. aureus species in 9 of the patients, all associated with IDU. Three patients died during hospitalization. The mRS score at discharge for survivors ranged 0-4.Conclusions: Patients with strokes from TVIE had heterogeneous presentations and putative mechanisms. We noted that robust neuroimaging is lacking for patients with TVIE from IDU and that such patients may benefit from neuroimaging as a screen for strokes to assist peri-operative management. Further inquiry is needed to elucidate stroke mechanisms in these patients.